The Influence of Economic Sustainability, Environmental Initiatives, and Farmers' Quality of Life on the Development of Social Entrepreneurship in the Agricultural Sector in West Java - Iwan Harsono; Ihsan Ro'is; Emi Salmah; Wahyunadi Wahyunadi (Westscience Press, 2023)
This study explores the relationship amongst farmers' quality of life, environmental initiatives, economic sustainability, and the growth of social entrepreneurship in the agricultural sector in West Java. The study investigates the correlations between these variables on a sample of 200 farmers using structural equation modeling. The results show a strong positive correlation between the growth of social entrepreneurship, environmental initiatives, farmers' quality of life, and economic sustainability. The study emphasizes how crucial it is to support a comprehensive and integrated strategy that takes into account farmer well-being, environmental sustainability, and economic stability in order to support the expansion of socially entrepreneurial endeavors in the agricultural sector.